Method for synergistically preparing alpha-Fe2O3 and byproduct polysilicate aluminum ferric material from industrial waste

By synergistically using copper slag, red mud and waste alkali liquid to prepare α-Fe2O3 and polymeric aluminum-ferrous silicate materials, the problems of low solid waste utilization rate and complex preparation process in the existing technology are solved, and efficient and low-cost high-value-added materials are achieved, with good environmental and economic benefits.

CN119954213APending Publication Date: 2025-05-09KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411984483.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-05-09

AI Technical Summary

Technical Problem

In the prior art, the comprehensive utilization rate of iron-containing solid waste and waste alkali liquid is low, the disposal technology has poor economic benefits, and the high-value utilization technology is lacking. The preparation process of α-Fe2O3 and polymeric aluminum silicate is complex, the operating cost is high, and secondary wastewater is easily generated.

Method used

By collaborating the copper slag, red mud and waste alkali liquid to prepare α-Fe2O3 by-product polymeric aluminum silicate material, the specific steps include mixed grinding, alkalizing and roasting, ultrasonic reaction, calcining, magnetic separation and acid regulation, etc., to achieve efficient preparation.

Benefits of technology

The value-added utilization of iron-containing solid waste and waste alkali liquid is achieved, the preparation cost is reduced, pollution is reduced, and high-grade α-Fe2O3 and polymeric aluminum-aluminum silicate materials are obtained, with good environmental and economic benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119954213A_ABST
    Figure CN119954213A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of industrial waste resource utilization, and discloses a method for preparing an alpha-Fe2O3 byproduct polysilicate aluminum ferric material through industrial waste collaboration.The method comprises the steps that copper slag and red mud are evenly mixed and ground, and a mixture A is obtained; adding waste alkali liquor into the mixture A to obtain a solid-liquid mixture B; carrying out alkalization roasting on the solid-liquid mixture B, then carrying out ultrasonic reaction and carrying out solid-liquid separation to obtain a solid precipitate C and a filtrate D; adding hydrogen peroxide into the solid precipitate C, and calcining to obtain a solid E; grinding the solid E, blending into ore pulp, and carrying out magnetic separation on the ore pulp to obtain alpha-Fe2O3 and mineral active micro powder F; and reacting the filtrate D under an acidic condition, and curing to finally obtain the polysilicate aluminum ferric material. According to the method, the copper slag, the red mud and the waste alkali liquor in the iron-containing solid waste are used as raw materials to replace pure chemical reagents to prepare the high-added-value material, the problems that the existing solid waste / liquid utilization rate is low, the disposal cost is high and the like are solved, and value-added utilization of the iron-containing solid waste and the waste alkali liquor is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of resource utilization of industrial waste, and in particular to a method for synergistically preparing α-Fe 2 O 3 A method for by-producing polyaluminium ferrosilicate material. Background Art

[0002] Iron-containing solid waste is mainly produced in the production process of the metallurgical industry. Its composition usually depends on its source, type and production process. It mainly includes red mud, copper slag, steel slag, iron tailings, etc. The comprehensive utilization of iron-containing solid waste in my country mainly includes re-selection, production of building materials, backfilling, reclamation, etc. However, due to the constraints of low resource grade, high utilization cost, poor economic benefits, lack of utilization technology and other problems, these solid wastes are still mainly stored. This disposal method not only occupies land, pollutes the environment, and is prone to geological disasters, but also causes serious waste of valuable components in solid waste. Among the bulk iron-containing solid waste, copper slag and red mud are rich in valuable elements such as iron, silicon and aluminum, which are suitable for the preparation of high value-added α-Fe 2 O 3 and polyaluminium ferrosilicate, but how to achieve α-Fe 2 O 3 The low-carbon, green and efficient preparation of polyaluminium ferrosilicate is an issue worthy of in-depth study.

[0003] Waste alkali liquor refers to high-concentration alkaline wastewater generated in the process of industrial production, which belongs to the hazardous waste (HW35 category) stipulated by the state. It mainly includes waste alkali liquor generated in fur tanning and product processing, pulp manufacturing, pharmaceuticals, chemical production and non-specific industries. Generally speaking, in addition to strong alkaline substances such as NaOH and KOH, waste alkali liquor may also contain some heavy metal ions and cyanide. These toxic substances pose a serious threat to human life and the ecological environment. At present, the main methods for the disposal of waste alkali liquor are electrolysis, acid-base neutralization, oxidation and biological methods. These methods are complex in process, easy to cause secondary pollution and have high disposal costs. It is worth mentioning that the strong alkaline substance in the waste alkali liquor is a valuable secondary alkali resource. How to efficiently and greenly utilize this strong alkaline substance is of great significance to the value-added utilization of waste alkali liquor and the sustainable development of the production industry.

[0004] α-Fe 2 O 3 It is the focus of research due to its unique quantum size effect, surface properties and macroscopic quantum tunneling effect. 2 O 3 Belongs to the hexagonal crystal cluster, the lattice edge lengths are: It is an n-type semiconductor with a band gap of 2.1eV. The conduction band is composed of Fe in the d orbital. 3+ The valence band is composed of Fe 3+and O2p on non-bonding orbitals. Compared with its iron oxide, α-Fe 2 O 3 The structure is relatively stable, and it has the advantages of corrosion resistance, high temperature resistance, strong adsorption and non-toxicity. Therefore, it is widely used in environmental governance, chemical catalysis, high-end instrument preparation and other fields. At present, many α-Fe 2 O 3 The mainstream synthesis methods are hydrothermal method, coprecipitation method, solid phase method, thermal decomposition method, solvothermal method, sol-gel method, aerosol method and template method. 2 O 3 The morphology, size and other microstructures are the key factors that determine its application performance. Therefore, different morphologies of α-Fe can be synthesized by different synthesis methods and controlling the raw material ratio. 2 O 3 However, these methods still have some challenges for large-scale production:

[0005] (1) Currently, α-Fe is mainly prepared using pure chemical reagents. 2 O 3 , high cost, complex process, low reactor utilization rate, and the particles are easy to agglomerate, uneven particle size and irregular morphology.

[0006] (2) Conventional preparation methods use water as the reaction medium, which will produce a large amount of waste liquid, increasing the environmental load and the production pressure of enterprises. The solvothermal method can realize the recycling of organic solvents, but the solubility of iron sources in organic solvents is poor, and the preparation process has limitations.

[0007] Polyaluminium ferric silicate is a new type of water-soluble polymer electrolyte with the characteristics of high ionicity, easy solubility in water, no gelation, and good hydrolysis stability. It is widely used in drinking water purification and industrial wastewater treatment, such as printing and dyeing wastewater, papermaking wastewater, pharmaceutical wastewater, and cadmium-fluorine radioactive pollution disposal. At present, polyaluminium ferric silicate is mainly prepared by chemical reagents, which is costly, complicated to operate, and easy to produce secondary wastewater. Therefore, it is of great significance to develop a reasonable, effective and green preparation method of polyaluminium ferric silicate.

[0008] In summary, it is necessary to study the synergistic preparation of α-Fe 2 O 3 The method of by-producing polyaluminium ferrosilicate material is used to solve the above technical problems. Summary of the invention

[0009] The main purpose of the present invention is to provide a method for preparing α-Fe 2 O 3 The method for producing by-product polyaluminium ferrosilicate material aims to solve the problems in the prior art of low comprehensive utilization rate of iron-containing solid waste and waste alkali liquor, poor economic benefits of disposal technology, lack of high-value utilization technology and α-Fe2 O 3 The preparation process of polyaluminium ferrosilicate is complex, the operating cost is high, and it is easy to generate secondary wastewater.

[0010] To achieve the above object, the present invention provides the following technical solutions:

[0011] Synergistic preparation of α-Fe from industrial waste 2 O 3 The method for by-producing polyaluminium ferrosilicate material comprises the steps of:

[0012] (1) uniformly mixing and grinding copper slag and red mud to obtain a mixture A for later use;

[0013] (2) adding waste alkali solution to mixture A to obtain a solid-liquid mixture B;

[0014] (3) alkalizing and roasting the solid-liquid mixture B, immersing the roasted product in water for ultrasonic reaction, and then separating the solid and liquid to obtain a solid precipitate C and a filtrate D;

[0015] (4) adding hydrogen peroxide to the solid precipitate C and calcining the solid to obtain a solid E;

[0016] (5) Grind the solid E and prepare it into slurry, and separate the slurry by magnetic separation to obtain α-Fe 2 O 3 and mineral active micro powder F;

[0017] (6) The pH of the filtrate D is adjusted to acidic and then subjected to a first reaction, and after the reaction is completed, the filtrate is allowed to stand and mature to obtain a filtrate H; then the pH of the filtrate H is adjusted to acidic and then subjected to a second reaction, and after the reaction is completed, the filtrate is allowed to stand and mature again to finally obtain a polyaluminum-iron silicate material.

[0018] Preferably, the mass ratio of the copper slag to the red mud in step (1) is (0.5-0.8):1; the mesh number of the ground and sieved mixture A is less than 325 meshes.

[0019] Specifically, the main components of copper slag are iron oxide and silicon oxide, wherein the content of iron oxide is ≥55% and the content of silicon oxide is ≥35%. The main components of red mud are iron oxide, silicon oxide, aluminum oxide and sodium oxide, wherein the content of iron oxide is ≥20%, the content of silicon oxide is ≥15-30%, the content of aluminum oxide is ≥30-40% and the content of sodium oxide is ≥10-20%.

[0020] Preferably, in step (2), the solid-liquid ratio of mixture A to waste alkali liquid is 1:(1-8.5) g / mL.

[0021] Preferably, the pH of the waste alkali liquid is ≥12. When the pH of the waste alkali liquid is lower than 12, the pH is increased to above 12 by evaporation concentration. The strong alkaline substance in the waste alkali liquid is NaOH, KOH, Ca(OH) 2 or Ba(OH) 2 At least one of .

[0022] Specifically, the waste alkali liquor is at least one of the waste alkali liquors generated in fur tanning and product processing, pulp manufacturing, pharmaceuticals, chemical production and non-specific industries.

[0023] Preferably, the alkalization roasting in step (3) is roasting at 400-800°C for 0.5-2h; the temperature of the water is 60-90°C, and the ultrasonic reaction time is 20-40min.

[0024] Preferably, in step (4), the molar ratio of the hydrogen peroxide to the iron in the solid precipitate C is 1:(1.2-1.8); and the calcination is carried out at a temperature of 500-600° C. for 2-5 hours.

[0025] Preferably, in step (5), the solid E is ground and sieved to a mesh size of less than 325 meshes, and the slurry concentration is 5-20%; and the magnetic field intensity during the magnetic separation is 800-1500 Oe.

[0026] Preferably, the α-Fe 2 O 3 Fe 2 O 3 Content ≥95%.

[0027] Preferably, during the first reaction in step (6), sulfuric acid is used to adjust the pH of the filtrate D to 3-4, the first reaction is stirred at 30-60° C. for 0.5-1.5 h, and the aging time is 4-8 h.

[0028] Preferably, during the second reaction in step (6), sulfuric acid is used to adjust the pH of the filtrate H to 2-2.5, and the second reaction is stirred at 50-80° C. for 0.5-1.5 h, and the aging time is 8-10 h.

[0029] The beneficial effects of the present invention are:

[0030] (1) The present invention utilizes copper slag, red mud and waste alkali liquor in iron-containing solid waste as raw materials to replace pure chemical reagents to prepare high value-added materials, thereby solving the problems of low utilization rate of existing solid waste / liquid and high disposal cost, and realizing the value-added utilization of iron-containing solid waste and waste alkali liquor, which has good environmental and economic benefits.

[0031] (2) The present invention makes up for the α-Fe 2 O 3The preparation process of polyaluminium ferrosilicate is complex, the environment is polluted, and the operating cost is high. This paper fills the gap of low-carbon green preparation of nano-α-Fe based on iron-containing solid waste and waste alkali liquid. 2 O 3 and polyaluminium ferrosilicate technology gap; obtain high-grade α-Fe 2 O 3 , its Fe 2 O 3 The content is greater than or equal to 95%.

[0032] (3) The mineral active micropowder obtained after alkaline roasting and magnetic separation contains Si, Ca, Al, Fe, etc., which can be used in cement, construction and other industries to maximize the utilization of iron-containing solid waste without secondary waste discharge. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The high-quality α-Fe obtained in Example 1 of the present invention 2 O 3 XRD pattern of

[0034] Figure 2 The high-quality α-Fe obtained in Example 1 of the present invention 2 O 3 Physical picture;

[0035] Figure 3 This is a physical picture of polyaluminium ferrosilicate according to Example 1 of the present invention. DETAILED DESCRIPTION

[0036] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0037] Example 1

[0038] The industrial waste provided in this embodiment is used to synergistically prepare α-Fe 2 O 3 The method for by-producing polyaluminium ferrosilicate material comprises the steps of:

[0039] S1: copper slag and red mud are uniformly mixed and ground into 400 meshes at a mass ratio of 0.5:1 to obtain a mixture A for later use;

[0040] S2: adding waste alkali solution produced in fur tanning and product processing with a pH of 13 to the mixture A obtained in S1 at a solid-liquid ratio of 1:1 g / mL to obtain a solid-liquid mixture B;

[0041] S3: placing the solid-liquid mixture B in a high-temperature reaction furnace at 400°C for alkalization and roasting for 2 hours, then immersing it in clean water at 60°C for 20 minutes for ultrasonic separation to obtain a solid precipitate C and a filtrate D;

[0042] S4: Add hydrogen peroxide to the solid precipitate C, Fe:H 2 O 2 The molar ratio of is 1:1.2, and calcined in a high temperature reaction furnace at 500°C for 2h to obtain a solid E;

[0043] S5: Grind the solid E to less than 325 mesh, prepare the ground solid E into a slurry with a concentration of 5%, and perform magnetic separation on the slurry at a magnetic field strength of 800Oe to finally obtain Fe 2 O 3 High-grade α-Fe with a content of 95.5% 2 O 3 and mineral active micro powder F;

[0044] S6: The pH of the filtrate D was adjusted to 4 using sulfuric acid, and the mixture was stirred at 30°C for 0.5 h and then allowed to stand for 8 h to obtain a filtrate H. The pH of the filtrate H was then adjusted to 2, and the mixture was stirred at 50°C for 1 h and then allowed to stand for 8 h to finally obtain a polyaluminum ferrosilicate material.

[0045] Among them, the main components of copper slag are iron oxide content of 65.3% and silicon oxide content of 48.4%; the main components of red mud are iron oxide content of 20.5%, silicon oxide content of 15.6%, aluminum oxide content of 40%, and sodium oxide content of 20%; the strong alkaline substances in the waste alkali liquid are NaOH and KOH.

[0046] The obtained polyaluminium ferrosilicate material was used for treating wastewater with an arsenic concentration of 1000 mg / L, and the arsenic removal rate was as high as 98.5%.

[0047] High-quality α-Fe 2 O 3 The XRD pattern of Figure 1 As shown by Figure 1 It can be seen that the final α-Fe 2 O 3 The main component of the product is α-Fe 2 O 3 The diffraction peak of FeCO was only observed at 2θ=31.81. 3 Diffraction peak.

[0048] High-quality α-Fe 2 O 3 The actual picture is as follows Figure 2 As shown by Figure 2 It can be seen that the final α-Fe2 O 3 The product is reddish brown powder.

[0049] The obtained polymerized aluminum iron silicate is shown in the figure below: Figure 3 As shown by Figure 3 It can be seen that the final polyaluminium ferrosilicate product is a yellow-black mixed powder.

[0050] Example 2

[0051] The industrial waste provided in this embodiment is used to synergistically prepare α-Fe 2 O 3 The method for by-producing polyaluminium ferrosilicate material comprises the steps of:

[0052] S1: copper slag and red mud are uniformly mixed and ground into a mixture of less than 325 meshes at a mass ratio of 0.8:1 to obtain a mixture A for later use;

[0053] S2: adding waste alkali liquid produced in pulp manufacturing and pharmaceutical manufacturing with a pH of 14 to the mixture A obtained in S1 at a solid-liquid ratio of 1:8.5 g / mL to obtain a solid-liquid mixture B;

[0054] S3: placing the solid-liquid mixture B in a high-temperature reaction furnace at 600°C for alkalization and roasting for 0.5h, then immersing it in 90°C clean water for 40min of ultrasonic treatment, and then separating the solid and liquid to obtain a solid precipitate C and a filtrate D;

[0055] S4: Add hydrogen peroxide to the solid precipitate C, Fe:H 2 O 2 The molar ratio of 1:1.8 was calcined in a high temperature reaction furnace at 600°C for 5h to obtain a solid E;

[0056] S5: Grind the solid E to less than 325 mesh, prepare the ground solid E into a slurry with a concentration of 20%, and perform magnetic separation on the slurry under a magnetic field strength of 1500Oe to finally obtain Fe 2 O 3 High-grade α-Fe with a content of 97.4% 2 O 3 and mineral active micro powder F;

[0057] S6: The pH of the filtrate D was adjusted to 3 using sulfuric acid, and the mixture was stirred at 60°C for 1.2 hours and then allowed to stand for 4 hours to obtain a filtrate H. The pH of the filtrate H was then adjusted to 2.5, and the mixture was stirred at 70°C for 0.7 hours and then allowed to stand for 10 hours to finally obtain a polyaluminum ferrosilicate material.

[0058] Among them, the main components of copper slag are iron oxide content of 58.6%, silicon oxide content of 43.6%; the main components of red mud are iron oxide content of 21.6%, silicon oxide content of 23.4%, aluminum oxide content of 33.7%, sodium oxide content of 16.5%; the strong alkaline substances in the waste alkali liquid are NaOH, KOH, Ca(OH) 2 and Ba(OH) 2 ;

[0059] Polyaluminium ferrosilicate material is used for the treatment of wastewater with an arsenic concentration of 1000 mg / L, with an arsenic removal rate of up to 99.2%.

[0060] Example 3

[0061] S1: copper slag and red mud are uniformly mixed and ground into 500 meshes at a mass ratio of 0.6:1 to obtain a mixture A for later use;

[0062] S2: adding waste alkali liquor produced in pharmaceutical and chemical production and non-specific industries to the mixture A obtained in S1 at a solid-liquid ratio of 1:3.2 g / mL; the waste alkali liquor has a pH of 11, and is concentrated to a pH of 14 by evaporation to obtain a solid-liquid mixture B;

[0063] S3: placing the solid-liquid mixture B in a high-temperature reaction furnace at 800°C for alkalization and roasting for 1.5 hours, and then immersing it in clean water at 80°C for 30 minutes for ultrasonic separation to obtain a solid precipitate C and a filtrate D;

[0064] S4: Add hydrogen peroxide to the solid precipitate C, Fe:H 2 O 2 The molar ratio is 1:1.6, and calcined in a high temperature reaction furnace at 550°C for 3h to obtain a solid E;

[0065] S5: Grind the solid E to less than 325 mesh, prepare the ground solid E into a slurry with a concentration of 15%, and perform magnetic separation on the slurry under a magnetic field strength of 1000Oe to finally obtain Fe 2 O 3 High-grade α-Fe with a content of 97.8% 2 O 3 and mineral active micro powder F;

[0066] S6: The pH of the filtrate D was adjusted to 3.5 using sulfuric acid, and the mixture was stirred at 50°C for 1.5 hours and then allowed to stand for 6 hours to obtain a filtrate H. The pH of the filtrate H was then adjusted to 2.1, and the mixture was stirred at 80°C for 0.5 hours and then allowed to stand for 9 hours to finally obtain a polyaluminum ferrosilicate material.

[0067] Among them, the main components of copper slag are iron oxide content of 59.9%, silicon oxide content of 41.2%; the main components of red mud are iron oxide content of 24.8%, silicon oxide content of 29.6%, aluminum oxide content of 30.5%, sodium oxide content of 11.7%; the strong alkaline substance NaOHCa(OH) 2 and Ba(OH) 2。

[0068] Polyaluminium ferrosilicate material is used for the treatment of wastewater with an arsenic concentration of 1000 mg / L, with an arsenic removal rate of up to 99.8%.

[0069] In summary, by using copper slag, red mud and waste alkali liquor in iron-containing solid waste as raw materials to replace pure chemical reagents to prepare high value-added materials, the existing problems of low solid waste / liquid utilization rate and high disposal cost are solved, and the value-added utilization of iron-containing solid waste and waste alkali liquor is realized, which has good environmental and economic benefits. 2 O 3 The preparation process of polyaluminium ferrosilicate is complex, the environment is polluted, and the operating cost is high. This paper fills the gap of low-carbon green preparation of nano-α-Fe based on iron-containing solid waste and waste alkali liquid. 2 O 3 and polyaluminium ferrosilicate technology gap; obtain high-grade α-Fe 2 O 3 , its Fe 2 O 3 The content is greater than or equal to 95%.

[0070] The specific implementation methods of the invention are described in detail above, but they are only examples, and the invention is not limited to the specific implementation methods described above. For those skilled in the art, any equivalent modification or substitution of the invention is also within the scope of the invention, therefore, the equalization, modification, improvement, etc. made without departing from the spirit and principle of the invention should be included in the scope of the invention.

Claims

1. A method for preparing α-Fe2O3 as a by-product of polyaluminium-iron silicate material from industrial waste, characterized in that: The steps include: (1) uniformly mixing and grinding copper slag and red mud to obtain a mixture A for later use; (2) adding waste alkali solution to mixture A to obtain a solid-liquid mixture B; (3) alkalizing and roasting the solid-liquid mixture B, immersing the roasted product in water for ultrasonic reaction, and then separating the solid and liquid to obtain a solid precipitate C and a filtrate D; (4) adding hydrogen peroxide to the solid precipitate C and calcining the solid to obtain a solid E; (5) grinding the solid E and preparing it into slurry, and subjecting the slurry to magnetic separation to obtain α-Fe2O3 and mineral active powder F; (6) The pH of the filtrate D is adjusted to acidic and then subjected to a first reaction, and after the reaction is completed, the filtrate is allowed to stand and mature to obtain a filtrate H; then the pH of the filtrate H is adjusted to acidic and then subjected to a second reaction, and after the reaction is completed, the filtrate is allowed to stand and mature again to finally obtain a polyaluminum-iron silicate material.

2. The method for preparing α-Fe2O3 as a by-product of polyaluminium-iron silicate material from industrial waste as claimed in claim 1, characterized in that: The mass ratio of the copper slag to the red mud in step (1) is (0.5-0.8):1; the mesh number of the ground and sieved mixture A is less than 325 meshes.

3. The method for preparing α-Fe2O3 as a by-product of polyaluminium-iron silicate material from industrial waste as claimed in claim 1, characterized in that: In step (2), the solid-liquid ratio of mixture A to waste alkali liquid is 1:(1-8.5) g / mL.

4. The method for preparing α-Fe2O3 as a by-product of polyaluminium-iron silicate material from industrial waste as claimed in claim 3, characterized in that: The pH of the waste alkali liquid is ≥12; the strong alkaline substance in the waste alkali liquid is at least one of NaOH, KOH, Ca(OH)2 or Ba(OH)2.

5. The method for preparing α-Fe2O3 as a by-product of polyaluminium-iron silicate material from industrial waste as claimed in claim 1, characterized in that: The alkalization roasting in step (3) is roasting at 400-800°C for 0.5-2h; the temperature of the water is 60-90°C, and the ultrasonic reaction time is 20-40min.

6. The method for preparing α-Fe2O3 as a by-product of polyaluminium-iron silicate material from industrial waste as claimed in claim 1, characterized in that: The molar ratio of the hydrogen peroxide to the iron in the solid precipitate C in step (4) is 1:(1.2-1.8); the calcination is performed at a temperature of 500-600° C. for 2-5 hours.

7. The method for preparing α-Fe2O3 as a by-product of polyaluminium-iron silicate material from industrial waste as claimed in claim 1, characterized in that: In step (5), the solid E is ground and sieved to a mesh size of less than 325 meshes, and the slurry concentration is 5-20%; and the magnetic field intensity during the magnetic separation is 800-1500 Oe.

8. The method for preparing α-Fe2O3 as a by-product of polyaluminium-iron silicate material from industrial waste as claimed in claim 1, characterized in that: The Fe2O3 content of the α-Fe2O3 in step (5) is ≥95%.

9. The method for preparing α-Fe2O3 as a by-product of polyaluminium-iron silicate material from industrial waste as claimed in claim 1, characterized in that: During the first reaction in step (6), sulfuric acid is used to adjust the pH of the filtrate D to 3-4. The first reaction is stirred at 30-60° C. for 0.5-1.5 h, and the aging time is 4-8 h.

10. The method for preparing α-Fe2O3 as a by-product of polyaluminium-iron silicate material from industrial waste as claimed in claim 1, characterized in that: During the second reaction in step (6), sulfuric acid is used to adjust the pH of the filtrate H to 2-2.

5. The second reaction is stirred at 50-80° C. for 0.5-1.5 h, and the aging time is 8-10 h.

Citation Information

Cited By

  • Method for treating arsenic in waste acid by electrochemically strengthening dissolution of iron ions

    CN120349009A